Baby Room Temperature and Humidity Control System Using Fuzzy Logic - Arifuddin, Rahman; Dirgantara, Wahyu; Sumarahinsih, Andrijani; Putri Intan Hafsari1, Rizky; Iqbal Maulana, Fairuz; Trisna Nugraha, Anggara; Arya Sobhita, Rama (Emitor: Jurnal Teknik Elektro, 2024)
The health and comfort of infants are highly sensitive to room environmental factors, particularly temperature and humidity, which play a critical role in supporting their well-being. Managing these factors becomes complex due to constant fluctuations in ambient conditions, necessitating the use of advanced technology to ensure stability and adaptability. This study explores the application of fuzzy logic in designing a temperature and humidity control system for infant rooms, aiming to maintain an optimal environment for infant care. Fuzzy logic offers a robust approach for handling variability, enabling precise adjustments based on a set of predefined rules and inputs. The system operates by processing real-time input values of temperature and humidity and producing adaptive responses through control outputs, such as cooler, heater, and blower settings. These adjustments are determined by a series of if-then rules that interpret the input conditions to produce the necessary responses. Experimental testing and evaluation confirm that the fuzzy logic-based control system effectively maintains room temperature and humidity within the desired range. The results indicate that this approach can successfully sustain a stable and comfortable environment, underscoring its potential application in enhancing infant health and comfort through controlled indoor climate conditions.